Integrative and complementary practices in dentistry: the perception of the attended individuals (Research, Society and Development, 2021)
The aim of the study was to understand the perception of patients attended in the Extension Project “Complementary Integrative Practices in Health: Acupuncture in Dentistry”, from the Faculty of Dentistry of the Federal University of Minas Gerais, regarding the outcome of treatment by Integrative Complementary Practices in Health. This is a qualitative research, with a study population was chosen for convenience, composed of patients assisted in the aforementioned Extension Project, in 2019. To obtain the data, the focus group strategy was used, which was initiated by the Question Advisor: “What was it like for you to be assisted in this Project of the Faculty of Dentistry of UFMG with the complementaty therapies?”. The interpretation of the patients' statements was conducted through content analysis, based on phenomenology. After the analysis, six main themes emerged: Prior knowledge of PICS; Main Complaint; Impact of care on biopsychosocial dimensions; Techniques used in the project; Perception of the effectiveness of the complementaty therapies and the search for the main complaint solution prior to the project. It was concluded that the participants, even with little knowledge about complementary therapies, explained the importance and effectiveness of the Extension Project, based on the perception of the positive results felt with the treatment by the complementaty therapies.